Transformation of Industry Management in the Rocket and Space Industry Based on Digital Technologies - Vasily Kupriyanovsky; Roman Stupin; Vladimir Sukhomlin; Konstantin Utolin (Современные информационные технологии и IT-образование)
In the article the main aspects, trends and approaches to digital transformation of the enterprises of the space-rocket industry of foreign countries are considered. The main initiatives of public administration in the field of digitalization of the foreign enterprises of the space-rocket industry are considered. As predictive condition of effective digitalization of the main, the administrative and supporting processes at the enterprises carrying out actions for transformation of system of sectoral management is considered: implementations of flexible forms of project management, forming of array structures, and development of technology cooperation and improvement of formats of interaction of the state, business and citizens. The main approaches and techniques of research of digital technologies and assessment of perspectives of their implementation in production and administrative processes of the foreign enterprises of the rocket and space industry are considered. The article compares the main approaches of international agencies to the practice of sectoral management. On the basis of studying of cases of digital transformation, the assessment of barriers and risks of implementation of through digital technologies at the enterprises of the rocket and space industry is given. The article also discusses methods for increasing the efficiency of sectoral management in the rocket and space industry, which form the basis of best international practices. The article also examines the possibilities of using the Model for analyzing the behavioral complexity of tense sociotechnical systems, which is based on the analysis of self-similarity processes that arise during changes, to mitigate the risks of introducing digital technologies and new management practices at enterprises of the rocket and space industry.